Right Isomerism - Ismet N. Oesman; Hindra Irawan S.; Bambang Mardiono; Sudigdo Sastroasmoro (Indonesian Pediatric Society, 1992)
A rare case of complex heart malformatrion with right isomerism in a full-term baby boy which was the first case published in Indonesia is reported. The patient was initially managed as a healthy baby, but on the 20th hours after delivery he repeatedly vomitted, and from the rontgenographic finding diagnosis at that time was duodenal atresia. During the duodenostomy operation the surgeon noticed that the spleen was absent. Cyanosis appeared after operation. Techocardiography and electrocardiography was done immediately, which showed complex cyanotic congenital heart disease. Diagnosis complex cyanotic congenital heart disease with right isomerism then was suspected. Unfortunately the baby died on the 12th day of admission. 1be cause of death was sepsis and anoxia because of complex cyanotic congenital heart disease. Autopsy findings confirmed the diagnosis of right isomerism (bilateral trilobes lung, bilateral right atrial appendages).